2004
DOI: 10.1111/j.1442-2042.2004.t01-1-00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemohormonal therapy as primary treatment for metastatic prostate cancer: A randomized study of estramustine phosphate plus luteinizing hormone‐releasing hormone agonist versus flutamide plus luteinizing hormone‐releasing hormone agonist

Abstract: Background: The present study was undertaken mainly to investigate whether chemohormonal therapy with estramustine phosphate plus luteinizing hormone-releasing hormone (LHRH) agonist has a more beneficial effect than the hormonal therapy with flutamide plus LHRH agonist for newly diagnosed patients with metastatic prostate cancer. Methods: A total of 57 patients with metastatic prostate cancer aged 59-80 years (median 74 years) were entered in the study and were randomized to the treatment of estramustine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…In fact some authors reported the superiority of combination of EMP and LHRH agonist to orchiectomy alone or androgen deprivation therapy for the patients with advanced Pca. 15,16,30 In this study, 4.9% of patients achieved pT0, which can be acceptable antitumor effect. No serious adverse events occurred and there were no toxicity-related deaths.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact some authors reported the superiority of combination of EMP and LHRH agonist to orchiectomy alone or androgen deprivation therapy for the patients with advanced Pca. 15,16,30 In this study, 4.9% of patients achieved pT0, which can be acceptable antitumor effect. No serious adverse events occurred and there were no toxicity-related deaths.…”
Section: Discussionmentioning
confidence: 92%
“…13,14 We have reported the active effect of luteinizing hormone-releasing hormone (LHRH) plus EMP for the patients with advanced Pca. 15,16 We expected that this combination may be applicable to neoadjuvant therapy for the patients with high-risk Pca.…”
Section: Introductionmentioning
confidence: 99%
“…Noguchi et al 13 conducted a randomized trial of combination therapy with an LH-RH agonist and flutamide vs EMP in patients with stage D2 progressive prostate cancer; they reported that there was no significant difference between the groups in overall survival, but that progression-free survival was significantly prolonged in the EMP + endocrine therapy group. We defined progression-free survival as three consecutive PSA measurements that did not show an increase.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have suggested that EMP offers better efficacy than standard hormonal therapy for high-grade, high-stage PC [7]. In addition, chemohormonal therapy with EMP plus castration has been recommended over MAB with antiandrogen plus castration in suppression of FSH and testosterone for metastatic PC [7].…”
Section: Discussionmentioning
confidence: 97%